Fauna parasitária de peixes oriundos de pesque-pagues do município de Franca, São Paulo, Brasil. II. Metazoários - Tavares-Dias, Marcos [UNESP]; Moraes, Flávio Ruas de [UNESP]; Martins, Maurício L. [UNESP]; Kronka, Sérgio N. [UNESP] (Sociedade Brasileira de Zoologia, 2001)
Metazoan fauna from cultivated fishes (N = 433) in two feefishing farm of Franca, State of São Paulo, Brazil, was studied during a period of April 1997 through March 1999. Specimens of piauçú Leporinus macrocephalus Garavello & Britski, 1988 (Anostomidae), pacu Piaractus mesopotamicus Holmberg, 1887 (Characidae), carp Cyprinus carpio Linnaeus, 1758 (Cyprinidae), Tillapia rendalli Boulenger, 1896 (Cichlidae), nile-tilapia Oreochromis niloticus Linnaeus, 1758 (Cichlidae), matrinxã Brycon cephalus Günther, 1869 (Characidae) and tambacu hybrid (male of P. mesopotamicus x female of Colossoma macropomum Cuvier, 1818) were collected. A total of 29.3% was parasitized by monogenean, 9.7% with crustacean (copepodits and adults of Lernaea cyprinacea Linnaeus, 1758 and Argulus sp.) and 1.6% with myxosporean (Henneguya piaractus Martins & Souza, 1997 and Myxobolus colossomatis Moinar & Békési, 1993).The most susceptible species to myxosporean infestation was P. mesopotamicus. L. macrocephalus and P. mesopotamicus that showed a higher susceptibility to Argulus sp infestation. It was not observed significant difference (P > 0.05) in the seasonal variation of L. cyprinacea infection of all species. L. macrocephalus, P. mesopotamicus and tambacu showed a great number of P. pillulare with no significant difference (P > 0.05) between them. Monogenean infections were observed in all examined species, without significant difference (P > 0.05) in the seasonal variation. Nevertheless, occurrence of monogenean was higher in P. mesopotamicus and lower in Nile-tilapia. By the other hand, parasites number collected from P. mesopotamicus was lower in the winter. Copepodits of L. cyprinacea were found in the gills of P. mesopotamicus, tambacu and L. macrocephalus. However, adults of L. cyprinacea were observed only in the P. mesopotamicus and tambacu.
Parasitic fauna of cultivated fishes in feefishing farm of franca, state of São Paulo, Brazil. II. Metazoans
Keywords: Crustacean; copepodits; freshwater fish; metazoans; monogenean; myxosporeans; Parasites; Helminths